MENGENAL POLA ASUH ORANG TUA DALAM PEMBENTUKAN AKHLAK ANAK - Mohammad Adnan (CENDEKIA: Jurnal Studi Keislaman, 2019)
Parenting patterns in shaping children's morals is something that is very urgent to be known together. This is useful for anyone, especially for parents and educators. Getting to know parenting patterns in shaping children's morals is none other than the main goal is to provide an understanding for us all in an effort to shape children's morals, especially in times like today. Where children today have lost their true identity as humans. Why do the authors say that children now have lost their identity as human beings, this is the case of many young people today who have an immoral attitude or do not have morals, be it to parents, friends, neighbors and even teachers. We have seen this in various media, there are children who kill their own parents, there are children who kill their teachers and even dare to bring sharp weapons to school against their teachers to fight. For this reason, this article is important to read so that we can recognize good parenting in educating children.